Vitamin B6, B9, and B12 Supplementation in Antipsychotic-Induced Akathisia: A Case Report and Comprehensive Review - Quddus Salam; Tiwik Koesdiningsih; Widyantari, Maya; Algristian, Hafid (Indonesian Scientific Publication, 2025)
Schizophrenia and related psychotic disorders pose a substantial global health burden, with treatment often complicated by antipsychotic-induced extrapyramidal side effects. Akathisia, characterized by profound inner restlessness and repetitive movements, is particularly distressing and frequently leads to medication non-adherence and relapse. This case report and comprehensive review details the management of a 30-year-old woman with schizoaffective disorder who developed severe akathisia following three months of risperidone therapy, resulting in treatment discontinuation. Upon readmission, a multimodal therapeutic strategy was implemented: risperidone was switched to aripiprazole, and adjunctive therapy included clobazam, trihexyphenidyl, folic acid (B9), and mecobalamin (B12). The clinical rationale extended beyond conventional management to incorporate targeted nutritional support, based on evidence that vitamin B6 modulates dopaminergic, serotonergic, and GABAergic pathways, while folate and B12 are crucial for one-carbon metabolism, homocysteine regulation, and neuroprotection. Following this integrated intervention, the patient's akathisia resolved, daily functioning stabilized, and treatment adherence was restored. This report provides an in-depth discussion of the synergistic neurobiological mechanisms through which B vitamins may alleviate akathisia, situates the findings within the broader context of nutritional psychiatry, and highlights the socio-economic relevance of this low-cost, low-risk adjunctive strategy for resource-limited settings. While current evidence remains preliminary, this case underscores the importance of early akathisia recognition and supports the integration of nutritional assessment and B-vitamin supplementation into personalized treatment plans for patients intolerant to standard therapies. Further randomized controlled trials are warranted to establish standardized dosing and identify patient subgroups most likely to benefit.